Three Extraordinary Dream Interpretations - Savaşkan Cem Bahadır (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
Sleep and dreams are two inseparable concepts. The issue of dreams and their interpretations dates back to 5000 B.C. When looked at chronologically, dream interpretations are seen to be found in Assyrian, Sumerian, and Egyptian civilizations. Dreams are mentioned in the chapters of the Qur’an and provide information about the future, and this has increased the importance given to dreams and dream interpretation. Books on dream interpretation in libraries consist of copyrighted and translated works. When dealing with translations, the Arabic work Tabir al Ro’oya [Interpretation of Dreams] written by Ibn Sirin is understood to be one of the most translated works. When looking at the dream interpretation works that are the subject of study, they are seen to be unlike the very voluminous ordinary interpretation books that classify dreams according to subject or that explain dreams based on the items, objects, and entities seen in the dream. When examining these works in terms of their contents, they are seen to have been written in a very simple language and to involve concepts from daily life. This creates the feeling that the authors had prepared the descriptions so that people could always relate to them. This study will provide some information about the terminology in the literature and then attempt to convey to the reader the text of three extraordinary idioms and information about these.